On the estimation of parameters, survival functions, and hazard rates based on fuzzy life time data. Issue 10 (19th May 2017) - Shafiq, Muhammad; Viertl, Reinhard
ABSTRACT: Life time data analysis is regarded as one of the significant out-shoots of statistics. Classical statistical techniques reckon life time observations as precise numbers and solely cover variation among the observations. In fact, there are two types of uncertainty in data: variation among the observations and the fuzziness. To this effect, the analysis techniques, which do not consider fuzziness and are only based on precise life time observations, use incomplete information; hence lead to pseudo results. This study aimed at generalizing parameters estimation, survival functions, and hazard rates for fuzzy life time data.